2017
DOI: 10.1111/jnc.14207
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination strategies in tauopathies and synucleinopathies

Abstract: Vaccination therapies constitute potential treatment options in neurodegenerative disorders such as Alzheimer disease or Parkinson disease. While a lot of research has been performed on vaccination against extracellular amyloid b, the focus recently shifted toward vaccination against the intracellular proteins tau and a-synuclein, with promising results in terms of protein accumulation reduction. In this review, we briefly summarize lessons to be learned from clinical vaccination trials in Alzheimer disease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 139 publications
0
27
0
3
Order By: Relevance
“…Moreover, T2D per se is associated with cognitive dysfunction that can range from subtle diabetes-associated cognitive decrements to pre-dementia and dementia [4]. On the other hand, AD has no successful treatment, and therapeutic efforts have been directed towards classical neuropathological features that include gamma-secretase modulators, BACE1 inhibitors, immunotherapy, or taubased therapies [5][6][7]. However, different limitations have been raised [8] reducing the presently approved treatments to acetylcholinesterase inhibitors and glutamate antagonist memantine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, T2D per se is associated with cognitive dysfunction that can range from subtle diabetes-associated cognitive decrements to pre-dementia and dementia [4]. On the other hand, AD has no successful treatment, and therapeutic efforts have been directed towards classical neuropathological features that include gamma-secretase modulators, BACE1 inhibitors, immunotherapy, or taubased therapies [5][6][7]. However, different limitations have been raised [8] reducing the presently approved treatments to acetylcholinesterase inhibitors and glutamate antagonist memantine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies focused on autoantibodies in blood, and both increased and decreased concentrations of autoantibodies have been described in PD patients as compared to healthy controls (see Braczynski et al . and Akthar et al . for references).…”
mentioning
confidence: 90%
“…Consequently, active and passive immunisation strategies using antibodies against Aβ have been developed for AD (Braczynski et al . ). One study using a passive immunisation strategy demonstrated a reduction in Aβ plaques and beneficial effects on cognition in AD patients (Sevigny et al .…”
mentioning
confidence: 97%
“…Ведущим подходом признается таргетная иммунотерапия в виде пассивной или активной иммунизации, направленной на деградацию агрегированного церебрального aSyn. Активная иммунизация заключается в использовании вакцин, содержащих короткие пептиды -гомологи aSyn в конъюгации с различными носителями (AFFITOPE, AFFiRiS); ее цель -индукция формирования антител к С-концевому участку белка aSyn [6]. К настоящему времени проведено исследование фазы I/II (безопасность) вакцины PD01A у 28 пациентов с БП, показавшее возможность индукции антител против aSyn при отсутствии существенных побочных эффектов, а также иммунологическую эффективность «бустерных» вакцинаций при общем периоде наблюдения до 3 лет после начальной иммунизации [15].…”
unclassified
“…Совсем недавно исследование I фазы с использованием вакцин PD01A и PD03A было проведено и у пациентов с другой формой синуклеинопатии -мультисистемной атрофией (при данном заболевании агрегаты aSyn формируются в олигодендроцитах): по итогам 52-недельного наблюдения показаны высокая безопасность данного подхода и стабильный иммунный ответна вакцину PD01A [16], в связи с чем в ближайшее время планируется старт следующей фазы клинических исследований PD01A. Интересно, что на соответствующих моделях in vivo делаются небезуспешные попытки вакцинации и против тау-белка, который при ряде паркинсонических синдромов является важной мишенью патологического процесса [6]. Разработке анти-тау терапиии ее клинической реализации чрезвычайно способствует возможность визуализации тау-радиофармпрепаратов при позитронной эмиссионной томографии [13].…”
unclassified